A Global Intellectual Property Waiver is Still Needed to Address the Inequities of COVID-19 and Future Pandemic Preparedness. (September 2022) - Amin, Tahir; Kesselheim, Aaron S.
In October 2020, India and South Africa submitted a proposal to the World Trade Organization (WTO) to suspend IP on all COVID-19 vaccines, therapeutics, and diagnostics until widespread vaccination could help achieve immunity among people in low- and middle-income countries. After 18 months, the final WTO Decision substantially watered down the original text proposed by India and South Africa, limiting it only to patents on vaccines and the use of protected clinical trial data for regulatory approval. We address why an IP waiver under TRIPS consistent with the one originally proposed by India and South Africa is still needed to not only meet the ongoing inequities of COVID-19, but also to ensure the right precedent for future equitable pandemic preparedness and other crises affecting the global South. To meet the multilateral goals of the WTO, an IP waiver as proposed by India and South Africa is still needed to increase manufacturing capability for vaccines, therapeutics, and other COVID-19 health-related technologies.